é€šè¿‡ç›´æŽ¥æ•™å¦æ³•æé«˜å¦ç”Ÿå¯¹åŠ¨è¯çš„æŽŒæ¡èƒ½åŠ› - Aropah, Yuni; ., Ina; ., Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
???????????????????????????????????????????Taruna Bumi Khatulistiwa??????????????46?????????????????????????????????????????????????????????????????????????????????????????????? ????????????????????????????????????????????????56????85?? ???? ?? ????? ??? Abstract: The purpose of this research is to know the effect of teaching with direct teacing method to the students and to understand reaction of student about it. This object of this research is TBK Senior High School Second Grade Students,with total students were 39 students. The reseach method are practice?test and (diaocha). The useful of directly teaching method using verb makes student more keen and exited in study, thus the student?s respond toward verb was really interested and active in class. Based on the result of the pre and post test the writer can said the ability of understanding of verb?s student makes an improvement on student?s ability. It can be seen based on their pre test, they could only reach 56 on their score but it become 85 in the post test.   Keyword: verbs direct teaching method grasp